Aerodynamic characterization of an Albatross wing for Bio-inspired unmanned aerial vehicle. (2021) - Nithiyapathi, C.; Sreelakshmy, PS.; Suman, M.
Abstract: The aerodynamic efficiency of any flying object depends largely on the shape of its wing. Albatross, the largest flying bird in terms of the aerodynamic efficiency, is researching the wing structure of birds. The wing of a flange is first modelled and comparable with other influenced wing types as well as to the conventional geometric shapes which includes the delta, elliptical and rectangular wing types. These studies will help to understand the effect of wing shape on aerodynamic efficiency of the UAVs. Airfoil and flight speed analyses are carried out under the same terms, taking into account the same aspect ratio (AR), span of the wing and its area. There is now growing need for UAVs with different military and civil capabilities for a fixed-wing aircraft. The novel ideas and concepts for developing the Unmanned Aerial Systems is gaining a lot of attention on the current era of development includes the autonomous missions, such as maritime and spatial exploration. It is important to note this will help to provide the pathways for production of an efficient drone with high aerodynamic efficiency.